Improvement in Photosynthetic Rate and Grain Yield in Super-High-Yield Maize (Zea mays L.) by Optimizing Irrigation Interval under Mulch Drip Irrigation - Dongping Shen; Guoqiang Zhang; Ruizhi Xie; Bo Ming; Peng Hou; Jun Xue; Shaokun Li; Keru Wang (Agronomy, 2020)
High yield is one of the important goals of crop production, and close planting and optimum irrigation systems are important agronomic practices for increasing maize (Zea mays L.) grain yield. However, little is known about the effect of optimal irrigation interval on the photosynthetic rate (Pn) and dry matter accumulation (DM) of closely planted super-high-yield maize under drip irrigation under mulch. Therefore, the objective of this study was to determine the effects of irrigation interval on the leaf Pn, DM, and grain yield of closely planted super-high-yield maize under mulch drip irrigation in the Xinjiang Uygur Autonomous Region, Northwestern China. A field experiment was conducted using three irrigation intervals in 2016—namely, six days (D6), nine days (D9), and 12 days (D12)—and five irrigation intervals in 2017—namely, three days (D3), six days (D6), nine days (D9), 12 days (D12), and 15 days (D15). The Xianyu 335 high-yield maize hybrid was used in the test; the planting density was set to 12×104 plants ha−1, and an optimal irrigation quota of 540 mm was used. The results showed that during the irrigation period, (1) the soil moisture content (SMC), DM, leaf Pn, and grain yield of treatment D6 were higher than for other irrigation intervals, (2) the leaf Pn and stomatal conductance (GS) of the leaves of treatments D3, D9, D12, and D15 were significantly correlated with the SMC of the 0–40 cm soil layer, and (3) the leaf Pn of treatment D6 was significantly positively correlated with SMC in the 0–60 cm soil layer but not significantly correlated with GS. Irrigation treatment D6 was found to maintain high SMC, provide a water environment favorable to the growth of maize, and increase the leaf Pn and DM, and thereby obtain maize grain yield (20.6–21.0 t ha−1). Therefore, an optimal irrigation interval could be beneficial for adjusting soil moisture, leaf Pn, and DM in order to increase maize grain yield with drip irrigation under mulch.